Gereja dan Negara: Refleksi atas Tantangan Masyarakat Indonesia dan Pancasila: Suatu Pendekatan Sosiologis - Seda, Francisia SSE (Jurnal Orientasi Baru, 2013)
Pancasila is basic for the life of the nation and society in Indonesia. The Church as an element in the Indonesian society has a specific contribution in this civic life. This contribution could not be separated from â€œnew relationshipâ€ between the elements of society-state-market. This new relationship is coloured by the dynamic of societal life after 1998, the new cultural bond, problems of poverty, environment damage and ongoing development. The Churchâ€™s contribution could be enlightement in various levels of societal life, such as, guide for social conduct, network creation, development that respons the peopleâ€™s need, development of the elements of society that is characterized by multiculturalism to achieve a just, prosper, and peaceful society.